2011
DOI: 10.2478/v10049-011-0005-7
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administered Melatonin and the Accumulation and Toxicity of Cadmium in the Bank Vole (Myodes Glareolus)

Abstract: Orally Administered Melatonin and the Accumulation and Toxicity of Cadmium in the Bank Vole (Myodes Glareolus)Animal gender and age significantly influence the accumulation and toxicity of heavy metals, including cadmium (Cd). The aim of this study was to determine the effect of orally administered melatonin (6 μg/ml), a known antioxidant and metal chelator, on Cd accumulation and toxicity in one month old females and males (young) and five months old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A number of studies suggest the protective effect of melatonin on the toxicity of cadmium (Chwełatiuk et al, 2006;El-Sokkary et al, 2010;Hussein et al, 2014). Chwełatiuk and Włostowski (2011) and Drąg-Kozak et al (2018) demonstrated a decrease in cadmium content in the kidney, liver, ovary and brain of animals exposed to this metal and melatonin. This hormone is also known to influence haematological parameters and immunevarious status of fish (Esteban et al, 2013;Aripin et al, 2018).…”
Section: Some Researchers Have Suggested That Cardiac Mitochondrial Vmentioning
confidence: 99%
“…A number of studies suggest the protective effect of melatonin on the toxicity of cadmium (Chwełatiuk et al, 2006;El-Sokkary et al, 2010;Hussein et al, 2014). Chwełatiuk and Włostowski (2011) and Drąg-Kozak et al (2018) demonstrated a decrease in cadmium content in the kidney, liver, ovary and brain of animals exposed to this metal and melatonin. This hormone is also known to influence haematological parameters and immunevarious status of fish (Esteban et al, 2013;Aripin et al, 2018).…”
Section: Some Researchers Have Suggested That Cardiac Mitochondrial Vmentioning
confidence: 99%